Relasi Parasosial pada Perempuan Dewasa Awal Penggemar Idola K-Pop - Siswoyo, Adelia Octavia; Daranindra, Kirana Candradita; Abidin, Zainal (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Indonesia is one of the countries with the highest number of K-Pop fans in the world with the most fans from young women. K-Pop idol devotees can feel that their idol is attached to them to form a parasocial relationship. Parasocial relationship is a one-way and pseudo relationship that is formed between a character or celebrity and the audience or fans. This study aims to obtain an overview of the parasocial relationships of early adult female K-Pop idol worshipers in Indonesia and the influence on their developmental tasks. Participants in this study were six young adult women who had parasocial relationships with one or more K-Pop idols. This study used a qualitative approach, with the data collection process through semi-structured interviews and using thematic analysis methods to process the data. The results of the study showed that all participants had a parasocial relationship with idol figures. The parasocial relationships that are formed have an impact on their developmental tasks, namely social relations, their perspectives towards problems and coping strategy. Even so, all participants can understand reasonable limits as well as the positive and negative impacts that are felt so they don't overdo it.